2016
DOI: 10.1080/09593330.2016.1196736
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the bottlenecks of anaerobic digestion of olive mill solid waste by two-stage fermentation

Abstract: Two-stage anaerobic digestion (AD) of two-phase olive mill solid waste (OMSW) was applied for reducing the inhibiting factors by optimizing the acidification stage. Single-stage AD and co-fermentation with chicken manure were conducted coinstantaneous for direct comparison. Degradation of the polyphenols up to 61% was observed during the methanogenic stage. Nevertheless the concentration of phenolic substances was still high; the two-stage fermentation remained stable at OLR 1.5 kgVS/m³day. The buffer capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…For example, Serrano et al [13] reported that the methane production in the anaerobic digestion of OMSW subjected to a thermal treatment at 170 • C and 1 h varied from 119 ± 30 mL CH4/(gVS•d) to 172 ± 60 mL CH4/(gVS•d) by reducing the OLR from 2 to 1 gVS/(L•d). Stoyanova et al [12] reported that the biomethanization of two-phase OMSW operated at stable conditions at an OLR of 0.76 gVS/(L•d), but the increase of the OLR up to 1.1 and 1.76 gVS/(L•d) affected the methane production and, finally, caused the total failure of the system. In the same way, Orive et al [22] also reported low methane production rates (77 mL CH 4 /(gVS•d) in the semi-continuous anaerobic digestion of diluted OMSW (COD: 60 g/kg) at high OLRs (around 3 gVS/(L•d).…”
Section: Methane Production At the Different Experimental Phasesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Serrano et al [13] reported that the methane production in the anaerobic digestion of OMSW subjected to a thermal treatment at 170 • C and 1 h varied from 119 ± 30 mL CH4/(gVS•d) to 172 ± 60 mL CH4/(gVS•d) by reducing the OLR from 2 to 1 gVS/(L•d). Stoyanova et al [12] reported that the biomethanization of two-phase OMSW operated at stable conditions at an OLR of 0.76 gVS/(L•d), but the increase of the OLR up to 1.1 and 1.76 gVS/(L•d) affected the methane production and, finally, caused the total failure of the system. In the same way, Orive et al [22] also reported low methane production rates (77 mL CH 4 /(gVS•d) in the semi-continuous anaerobic digestion of diluted OMSW (COD: 60 g/kg) at high OLRs (around 3 gVS/(L•d).…”
Section: Methane Production At the Different Experimental Phasesmentioning
confidence: 99%
“…Among the processes to stabilize OMSW, anaerobic digestion offers the possibility of obtaining methane, as an energy carrier, and the possibility to recover the remaining digestate as fertilizer [10,11]. According to Stoyanova et al [12], stable single-stage semi-continuous OMSW anaerobic digestion proceeded at an organic loading rate (OLR) of 0.76 kgVS/(m 3 d) (VS, total volatile solids). Recently, Serrano et al [13] determined that the accumulation of VFA was the main reason for destabilization during anaerobic digestion of OMSW subjected to a thermal pre-treatment (1 h at 170 • C) at an OLR of 2 gVS/(m 3 •d).…”
Section: Introductionmentioning
confidence: 99%
“…Several treatment processes have been proposed to address this issue, including physicochemical procedures such as coagulation/flocculation [11], adsorption [12] or electrocoagulation [13], aerobic and anaerobic biological processes [14][15][16], as well as a wide range of advanced oxidation processes (AOPs), namely ozonation [17], Fenton-based [18], photocatalytic [19] or electrochemical [20] processes. However, the applicability and efficiency of AOP single-step units is often limited by OMW characteristics, as influent values of chemical and biochemical oxygen demand (COD, BOD 5 ) and total suspended solids (TSS) may be as high as 200, 100, and 35 g/L, respectively [21].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, some authors have proposed the use of two-stage AD for OMSW, where a first acidification stage is carried out to enhance the hydrolysis of the substrate. 39,40,42 The methane production rate obtained through twostage AD widely varied from 200 to 370 mL CH4/(g VSꞏd) ( Table 1). Therefore, the implementation of an acidification stage is likely not attractive for OMSW as the achieved methane productions were in the same range than for the single-stage AD.…”
Section: Review Of the Anaerobic Digestion Of Omswmentioning
confidence: 99%
“…On these studies, higher OLRs usually implied the inhibition of the process by the accumulation of volatile fatty acids and phenolic compounds. 35,42,44 Other authors reported operations at much higher OLRs than 1 g VS/(L reactor •d) without compromising reactor performance, although in most of the cases the experimentation time was less than 2 hydraulic retention times per condition, [36][37][38]41 which may not be enough for triggering the inhibition of the anaerobic digestion process.…”
Section: Review Of the Anaerobic Digestion Of Omswmentioning
confidence: 99%